Meningkatkan Kemampuan Berbicara Pada Anak Melalui Vidio Interaktif - Hesti Mayasari; Nur Halimah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Currently, education for early childhood is developing rapidly, which can be seen from the various media used by teachers. This research aims to explore the use of interactive videos as a learning medium in improving the language skills of young children. Interactive videos are considered an innovative and interesting medium for children because they present material with cute animated images, historical folklore and interesting musical instruments. This research uses qualitative methods with a literature study approach. The research results show that learning through interactive videos can increase children's enthusiasm for learning, develop critical thinking skills, and help children be more confident in expressing their opinions on a topic.